THE ROLE OF LOCAL GOVERNMENT IN SUPPORTING THE SUSTAINABILITY OF LEMANG MSMES AFTER THE OPERATION OF THE TRANS SUMATRA TOLL ROAD - Fretty Indahyani; R. Sally Marisa Sihombing (Yayasan Wayan Marwan Pulungan, 2026)
The development of large-scale infrastructure, such as toll roads, is expected to stimulate regional economic growth; however, it may also generate unintended negative impacts on local Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of local government in supporting the sustainability of lemang MSMEs in Tebing Tinggi City following the operation of the Trans Sumatra Toll Road. A descriptive qualitative research design was employed, using in-depth interviews with government officials and lemang MSME owners, supported by observation and document analysis. Data were analyzed through an interactive qualitative approach involving data reduction, data display, and conclusion drawing, with government performance examined through an organizational behavior perspective encompassing motivation, leadership, communication, organizational culture, and decision-making. The results indicate that the operation of the Trans Sumatra Toll Road has significantly reduced customer access and daily turnover of lemang MSMEs, with average income declining by up to 50 percent. Although the local government has implemented several support measures, including administrative facilitation and limited promotional activities, these interventions have not been sufficient to ensure MSME sustainability. The findings reveal weaknesses in adaptive leadership, effective communication, flexible decision-making, and innovation-oriented organizational culture within the responsible government agency. This study concludes that strengthening organizational behavior dimensions within local government institutions is essential to mitigate the negative impacts of infrastructure development and to enhance the sustainability of traditional MSMEs. The findings provide practical insights for policymakers in designing more adaptive and inclusive MSME development strategies amid structural economic changes.